Perkembangan dan Tantangan Pasar Modal Dalam Perekonomian Negara Indonesia - Audi M, Neysa; Mitra, Rifa; Munawarah, Lathifa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The capital market is an indicator of the country's economic progress. The capital market has a role as a main source of financing and not just making it an alternative substitute in the economy. The research objective is to identify developments and challenges faced by the capital market in the Indonesian economy. The writing method used by the author is a literature review sourced from journal references from 2019-2023 related to the theme of capital market developments and challenges in Indonesia. Based on the results of the literature review carried out, it was found that the development of the capital market in Indonesia is growing rapidly from year to year. The development of the capital market in Indonesia is very promising in terms of great opportunities which make it strong in the aspect of the middle class in Indonesia as a starting point for investment. This of course has challenges in the form of the total number of issuers on the Indonesia Stock Exchange (BEI) having very few that perform well. This encourages Indonesia to need issuers that have good quality and large scale which do not just obtain capital from the public.